Common Law Marriage and Teen Births - Shoshana Grossbard; Victoria Vernon (Institute for the Study of Labor (IZA), 2015)
Using microdata from Current Population Survey Fertility supplements 1990-2010 we examine whether Common Law Marriage (CLM) laws in the US affect teen birth rates. CLM effects are identified through cross-state and time variation, as four states repealed the law over the period of study. We find that in the states where CLM laws were first available but then repealed the odds that teens would become new mothers increased, with a larger increase among young black teens. When we include dummies for CLM at various times around the timing of the repeal, it turns out that the likelihood of becoming a mother is most affected by availability of CLM between 1 and 4 years prior to the repeal. There is a small negative effect of CLM on older women becoming mothers. To the extent that they reduce teen births CLM laws are socially desirable and worthy of further study.
Keywords: J12; J13; K36; 330; fertility; Common-Law marriage; teens